Health literacy among young adults: a short survey tool for public health and health promotion research - (:unkn) unknown (OXFORD UNIV PRESS, 2015)
Health literacy (HL) is context-specific. In public health and health promotion, HL in the private realm refers to individuals' knowledge and skills to prevent disease and to promote health in everyday life. However, there is a scarcity of measurement tools explicitly geared to private realm contexts. Our aim was to develop and test a short survey tool that captures different dimensions of HL in the context of family and friends. We used cross-sectional data from the Swiss Federal Surveys of Adolescents from 2010 to 2011, comprising 7983 males and 366 females between 18 and 25 years. HL was assessed through a set of eight items (self-reports). We used principal component analysis to explore the underlying factor structure among these items in the male sample and confirmatory factor analysis to verify the factor structure in the female sample. The results showed that the tested item set represented dimensions of functional, interactive and critical HL. Two sub-dimensions, understanding versus finding health-relevant information, denoted functional HL. Interactive and critical HL were each represented with two items. A sum score based on all eight items (Cronbach's alpha: 0.64) showed expected positive associations with own and parental education among males and females (p < 0.05). The short item set appears to be a feasible measurement tool to assess HL in the private realm. Its broader application in survey studies may help to improve our understanding of how this form of HL is distributed in the general population.
Keywords: health literacy; measurement; youth; public health; SUBSTANCE USE; OLDER-ADULTS; COMMUNICATION; ADOLESCENTS; INSTRUMENT; RISK